DIVERGENSI HAK KONTROL DAN HAK ARUS KAS TERHADAP COST STICKINESS : MODERASI KUALITAS AUDIT DAN INDEPENDENSI DEWAN KOMISARIS PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Christian Boardes Nathanael Siburian; Nur Cahyonowati (Diponegoro Journal of Accounting, 2026)
This study investigates how divergence between control rights and cash flow rights affects cost stickiness in Indonesian manufacturing firms listed on the IDX from 2015–2024, moderated by audit quality and board independence. Concentrated ownership in Indonesia often leads to disproportionate voting power, exacerbating agency conflicts in cost management. Using secondary data from 62 firms (620 observations) and EGLS regression, it measures cost stickiness via Anderson et al. (2003) and divergence as the rights gap for ultimate controllers.Findings show divergence significantly reduces cost stickiness, implying more flexible cost adjustments and potential earnings manipulation, consistent with Oh and Choi (2025). Big 4 audit quality moderates the control rights–stickiness link without direct effects, while board independence moderates both rights' pathways. The F-test confirms joint significance, but low Adjusted R² (16.64%) indicates other unmodeled factors.